2013
DOI: 10.1007/s12664-013-0357-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequential therapy versus standard triple-drug therapy for Helicobacter pylori eradication: A randomized study

Abstract: Sequential therapy was significantly better than standard therapy for eradicating H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…A total of 27 full articles and conference abstracts were further assessed for eligibility. After exclusion of trials that used modified sequential therapy ( n = 7) and those included paediatric patients ( n = 7), a total of 13 trials including 5173 patients were eligible for inclusion in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 27 full articles and conference abstracts were further assessed for eligibility. After exclusion of trials that used modified sequential therapy ( n = 7) and those included paediatric patients ( n = 7), a total of 13 trials including 5173 patients were eligible for inclusion in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…Besides, several other randomised trials comparing sequential therapy for either 10 or 14 days with triple therapy for 14 days have been reported after the meta‐analysis by Gatta et al . in 2013 . More importantly, none of the previous meta‐analyses included sequential therapy given for 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…18,24,25 For example, Fakheri and colleagues 18 , reported an eradication rate of 84% by ITT analysis for clarithromycin in quadruple therapy regimen. On the other hand, in contrast to our findings, there are several surveys declared that gemifloxacin was an effective antibiotic for H. pylori eradication.…”
Section: Discussionmentioning
confidence: 99%
“…This regimen includes a PPI and amoxicillin for 5 d, followed by a PPI, clarithromycin, and tinidazole triple therapy for another 5 d. Several studies have indicated that the eradication rate of sequential therapy was significantly higher than that of STT [85][86][87] . The reason that sequential therapy has a higher eradication rate than STT is that amoxicillin and PPI administered during the first 5 d decreases H. pylori density in the stomach, which increases clarithromycin and metronidazole efficacy [32,[88][89][90] .…”
Section: Are There Suitable Sequential and Concomitant Therapy Alternmentioning
confidence: 99%